Valuation of Closely Held Stocks -- A Recent Decision [2] - Weiss, Debra (The CPA journal (1975), 1987)
The proper valuation of the common stock of a closely held corporation is important for determining estate and gift taxes or income taxes when the business is sold or reorganized. In the 1986 Tax Court case of The Northern Trust Co. et al. versus Commissioner, the Internal Revenue Service claimed that the 4 minority stockholders of Curran Contracting Co. had underpaid federal taxes due to the improper valuation of identical blocks of Class A and Class B common stock placed in trusts in 1976. In reaching a valuation for the stock, the judge rejected the use of the taxpayers' market comparable approach in favor of the discounted cash flow approach, but he upheld the validity of the taxpayers' capital asset pricing model to determine the cost of capital. The judge also rejected the taxpayers' determination of a minority discount as the inverse of premiums for control calculated from public tender offers. However, the judge supported a 25% minority discount and a 20% discount for lack of marketability.